High Performance of CSI Fed IM Drives at Low Speed operation with MRAS Based Estimation of Stator Resistance - selvam, N.Panneer; Rajasekaran, V. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This paper is proposed to improve the performance of sensorless vector controlled CSI fed induction motor drives during low-speed operations. In general the performance of sensorless vector controlled induction motor drives is poor at very low speed due to stator resistance variations and the estimated flux and torque deviates from its set value. Therefore online tuning of the stator resistance is necessary at very low speed. The performance and efficiency of an induction motor drive system can be enhanced by online tuning of stator resistance. A novel model reference adaptive system (MRAS)-based algorithm for simultaneous identification of stator resistance (Rs) and rotor speed (ðŽr) implemented in sensorless Field oriented controlled CSI fed induction motor. The reference model and adjustable model are interchangeable for concurrent ðŽr and Rs estimation in the low-speed operating region is investigated. The simulation and experimental results are proved that the proposed method is improving the performance of the drive system at low speed operation.